Lovely Blossom Sdn Bhd / Muhammad Yusniza Yunus, Aslin Abd Sani, Nor Hafizah Zainal Arif ... [et.al] - Yunus, Muhammad Yusniza; Sani, Aslin Abd; Zainal Arif, Nor Hafizah; Mohd Idris, Norehan; Rosli, Norafidah (Faculty of Hotel and Tourism Management, 2006)
Usually, in such organization, administration department plays an important role in ensuring the business to run smoothly and systematicaEy. This administration plan is one of the plans in our business organization. Our company may face a lot of problem without this administration functions. This plan is a total control to this organization so that we can result in the highest level of productivity and services in effective and efficient ways. Each organization in the business has it own objectives and mission as to improve the business capability. This objectives and missions also are needed to make sure the establishment the business achieves its aim to become firm and popular in this field.